Peranan Guru Mata Pelajaran Fikih Dalam Meningkatkan Kedisiplinan Shalat Berjemaah Lima Waktu Siswa Kelas VII MTs Swasta Al-Washliyah Stabat - Muhammad Supawi; Ayub Wiranda (EduInovasi: Journal of Basic Educational Studies, 2021)
This research found at least several problems such as the role of the Fiqh subject teacher in carrying out learning and teaching activities for students in grade VII MTs. Private Al-Washliyah Stabat, the implementation of the five daily prayers in congregation by class VII MTs students. Private Al Washliyah Stabat and the role of fiqh subject teachers in increasing discipline in doing congregational prayers for class VII MTs students. Private Al Washliyah Stabat. This study aims to determine the role of the Fiqh subject teacher in carrying out learning and teaching activities for students in class VII MTs. Private Al-Washliyah Stabat. Knowing the implementation of the five daily prayers in congregation by class VII MTs students. Private Al Washliyah Stabat. as well as the extent to which the role of the Fiqh subject teacher in increasing discipline in performing congregational prayers for seventh grade students of MTs. Private Al Washliyah Stabat. This type of research is qualitative research, namely research procedures that produce descriptive data in the form of written or spoken words from people and observable behavior. From the results of completeness above, it can be explained that at the pre-Meeting 29.7% of students who got a complete score in the field of Jurisprudence, at Meeting I increased to 46% of students who completed Fiqh learning activities on the material of understanding congregational prayer. At the second meeting the level of completeness of students in learning fiqh was 78.3% of class VII MTs. Private Al-Washliyah Stabat. Then analyzed from Meeting III, student completeness reached 100%.